Nutrient and Stress Sensing in Pathogenic Yeasts - Rutherford, Julian C.; Bahn, Yong-Sun; van den Berg, Bert; Heitman, Joseph; Xue, Chaoyang (Frontiers in Microbiology, 2019)
More than 1.5 million fungal species are estimated to live in vastly different environmental niches. Despite each unique host environment, fungal cells sense certain fundamentally conserved elements, such as nutrients, pheromones and stress, for adaptation to their niches. Sensing these extracellular signals is critical for pathogens to adapt to the hostile host environment and cause disease. Hence, dissecting the complex extracellular signal-sensing mechanisms that aid in this is pivotal and may facilitate the development of new therapeutic approaches to control fungal infections. In this review, we summarize the current knowledge on how two important pathogenic yeasts, Candida albicans and Cryptococcus neoformans, sense nutrient availability, such as carbon sources, amino acids, and ammonium, and different stress signals to regulate their morphogenesis and pathogenicity in comparison with the non-pathogenic model yeast Saccharomyces cerevisiae. The molecular interactions between extracellular signals and their respective sensory systems are described in detail. The potential implication of analyzing nutrient and stress-sensing systems in antifungal drug development is also discussed.